MÔ HÌNH KINH DOANH CÙNG NGƯỜI SẢN XUẤT QUY MÔ NHỎ: Bộ công cụ Phương pháp LINK (Bản rút gọn) - Sopov, Monika; Lundy, Mark M.; Even, Brice; Huong, Pham Thu (International Center for Tropical Agriculture, 2014)
This is an abridged version of LINK Methodology in Vietnamese. LINK can help your business facilitate a systematic learning process between actors from a selected value chain, and discover new opportunities for innovation, based on the application of a partici¬patory toolkit, with four main tools: (1) The value chain map, used to understand the macro context of markets and the businesses which link rural producers with buyers; (2) The business model canvas, used to understand in more detail each business which links rural producers with buyers; (3) The New Business Model principles, used to determine whether each business which links rural producers with buyers is truly inclusive; and (4) The prototype cycle, used to continuously improve the inclusivity of every business which links rural producers with buyers.